2014
DOI: 10.1091/mbc.e14-02-0735
|View full text |Cite
|
Sign up to set email alerts
|

Cby1 promotes Ahi1 recruitment to a ring-shaped domain at the centriole–cilium interface and facilitates proper cilium formation and function

Abstract: Cby1 localizes to centrioles and antagonizes canonical Wnt signaling. Cby1−/− mice have cystic kidneys, and Cby1 facilitates primary cilium formation and ciliary recruitment of Arl13b. Cby1 localizes to a distal centriolar domain with Ofd1 and Ahi1, and the amount of Ahi1 at the transition zone is reduced in Cby1−/− cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 73 publications
(113 reference statements)
7
63
0
Order By: Relevance
“…3C). FAM92A showed extensive colocalization with Cby1 at mother centrioles while displaying a partial overlap with CEP164, which localizes to the distal appendages of mother centrioles (5,6,14,15,20). Furthermore, the results from costaining with different centrosome/centriole markers, including G-tub (centrosomes), CEP135 (proximal ends of centrioles), and centrobin (daughter centrioles), support the notion that FAM92A localizes to the distal end of mother centrioles.…”
Section: Identification Of Fam92a As a Cby1-interacting Proteinsupporting
confidence: 61%
See 2 more Smart Citations
“…3C). FAM92A showed extensive colocalization with Cby1 at mother centrioles while displaying a partial overlap with CEP164, which localizes to the distal appendages of mother centrioles (5,6,14,15,20). Furthermore, the results from costaining with different centrosome/centriole markers, including G-tub (centrosomes), CEP135 (proximal ends of centrioles), and centrobin (daughter centrioles), support the notion that FAM92A localizes to the distal end of mother centrioles.…”
Section: Identification Of Fam92a As a Cby1-interacting Proteinsupporting
confidence: 61%
“…Chibby1 (Cby1) is a conserved 15-kDa coiled-coil protein that predominantly localizes to mother centrioles/basal bodies and plays a pivotal role in the formation and function of cilia (6,(12)(13)(14)(15)(16)(17)(18)(19). Cby1 knockout (Cby1-KO) mice display several hallmarks of ciliary defects, including chronic upper airway infection (12), subfertility, and polycystic kidneys (15) as well as polydactyly and hydrocephalus at low frequencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Cby1 localizes to the base of cilia and plays a crucial role in ciliogenesis. [18][19][20][21][22] More recently, we demonstrated that, during differentiation of airway ciliated cells, Cby1 localizes to nascent centrioles and interacts with Rabin8, a guanine nucleotide exchange factor (GEF) for the small GTPase Rab8 to promote Rab8 recruitment for efficient assembly of membranous structures, called ciliary vesicles, at the distal end of centrioles. 18 Intriguingly, Rab8 has been shown to regulate cell shape, and expression of dominant-negative Rab8 mutants or depletion of Rab8 by small interfering (si) RNAs promotes an epithelial cell-like morphology including tight cell-cell contacts and actin stress fiber formation.…”
Section: Discussionmentioning
confidence: 99%
“…Cby1 also plays a crucial role during ciliogenesis, likely independent of b-catenin signaling. [18][19][20][21][22] Using human colon adenocarcinoma SW480 cells in which APC is mutated, we reported that stable expression of wildtype Cby1, but not a 14-3-3-binding-defective mutant (Cby1S20A), results in cytoplasmic translocation of b-catenin, concomitant with a reduction in b-catenin signaling and cell growth. 23 These results suggest a role for Cby1 as a tumor suppressor in colon cancer.…”
Section: Introductionmentioning
confidence: 99%